Criminal liability for breach of fiduciary duty: a case of criminal breach of trust by the personal representative of the deceased’s estate - Halim, Akmal Hidayah; Mohd Noor, Nor Azlina (UPM Press, 2015)

(untitled)
The governing law on the administration of estate in Malaysia requires an appointment of a personal representative before a deceased’s estate can be dealt with. The personal representative acts as a fiduciary and is empowered to take possession and control over of the estate. However, in the hands of unscrupulous personal representative, the estate might be dishonestly used or misappropriated. In such a case, the personal representative could be charged for criminal breach of trust as provided by the Malaysian Penal Code and would therefore be punished with imprisonment, whipping and fine. This paper aims to examine whether such punishment is adequate in regulating the conducts of the personal representative and remedying the estate beneficiaries against the misconducts of such personal representative. The study adopts the doctrinal analysis by examining the existing primary and secondary materials including statutory provisions as provided the Probate and Administration Act 1959 (Act 97) and the Penal Code (Act 574) , case law and other legal and non-legal literatures relating to the adequacy of the relevant law. The article finds that once the estate has been misappropriated, charging the personal representative and punishing him for criminal breach of trust are inadequate and will not give much benefit to the estate beneficiaries. The punishment should be extended to depriving the personal representative of his own property so that the rights of the estate beneficiaries as the vulnerable party are better protected.